Byzantium : Capital of an Ancient Empire. - Morgan, Giles (Oldcastle Books, 2007)
So what's so significant about the Byzantine Empire? It is now recognized as having had a considerable influence on the Renaissance and a significant impact in the shaping modern Europe. Modern historians are increasingly acknowledging the role the Byzantine Empire played in the development of both Islam and Christianity, and the relationship between the two. The term 'Byzantine' derives from the ancient Greek city of Byzantium founded in 667 BC by colonists from Megara. It was named in honor of their leader Byzas. It later became better known as Constantinople, that gateway between West.